2017
DOI: 10.1002/2017ja024351
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of high‐energy (>150 keV) heavy ion intensities in Earth's middle to outer magnetosphere

Abstract: Previous observations have driven the prevailing assumption in the field that energetic ions measured by an instrument using a bare solid state detector (SSD) are predominantly protons. However, new near‐equatorial energetic particle observations obtained between 7 and 12 RE during Phase 1 of the Magnetospheric Multiscale mission challenge the validity of this assumption. In particular, measurements by the Energetic Ion Spectrometer (EIS) instruments have revealed that the intensities of heavy ion species (spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 83 publications
8
18
0
Order By: Relevance
“…While He ++ only reaches a peak relative abundance near 10% (Figures e, f, and h, red line), He ++ does reach higher abundances than other minor species within the magnetosphere (i.e., He + and H 2 + ; Figures e, f, and h, green and blue lines, respectively). This is similar to studies at Earth which found the abundance of solar wind‐originating O 6+ surpassing that of ionospheric‐originating O + for high energies in the outer magnetosphere (Allen et al, ; Cohen et al, ). The distribution of He + follows closely with He ++ , consistent with He + originating largely from charge exchange with He ++ as well as from interplanetary pickup ions in the solar wind (Hamilton et al, ; Möbius et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…While He ++ only reaches a peak relative abundance near 10% (Figures e, f, and h, red line), He ++ does reach higher abundances than other minor species within the magnetosphere (i.e., He + and H 2 + ; Figures e, f, and h, green and blue lines, respectively). This is similar to studies at Earth which found the abundance of solar wind‐originating O 6+ surpassing that of ionospheric‐originating O + for high energies in the outer magnetosphere (Allen et al, ; Cohen et al, ). The distribution of He + follows closely with He ++ , consistent with He + originating largely from charge exchange with He ++ as well as from interplanetary pickup ions in the solar wind (Hamilton et al, ; Möbius et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the magnetosphere of Earth (Allen et al, ; Allen, Livi, & Goldstein, ; Allen, Livi, Vines, et al, ), the spatial distribution of He ++ is consistent with entry through both Dungey‐cycle related reconnection and Kelvin‐Helmholtz Instabilities. The outer magnetotail (>30 R S ) has similar intensities of H 2 + and He ++ when integrated over all (32–220 keV) energy channels (Figures c and e). This is reminiscent of results at Earth; for example, Cohen et al () found the abundances of solar wind O 6+ exceed that of ionospheric‐originating O + in the outer magnetotail (>7 R E ) for energies above 150 keV. This suggests that a heightened abundance of solar wind ions in planetary magnetotails may be a common occurrence—however, more comparisons to other magnetospheres, such as at Jupiter, should still be made. That the densities of W + , H + , H 2 + , He + and He ++ in the magnetotail are observed to minimize near midnight in the outer magnetosphere (>30 R S ) is likely an orbital effect due to the plasma sheet being displaced from Cassini's location in the geographic equatorial plane during the years 2005–2007, when much of the distant magnetotail observations were made. Larger W + density at the dusk magnetotail flank indicates that W + experiences more loss processes than generation processes (for the energy range of 32 to 220 keV) as it rotates across the magnetotail.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, examining characteristics of ionosphere oxygen outflows is critical for modeling magnetotail dynamics. Most oxygen ion observations in the magnetotail are focused on the central plasma sheet, where these ions have already been energized (Cohen et al, 2017;Kistler & Mouikis, 2016;Kronberg et al, 2015;Slapak et al, 2017) by various acceleration mechanisms operating in this region (Bosqued et al, 2009;Keika et al, 2013;Kronberg et al, 2014). Much less is known about oxygen outflows Our study of oxygen outflows around the plasma sheet boundary supplements previous investigations on oxygen ions in the plasma sheet (Kistler & Mouikis, 2016;Kronberg et al, 2015;Maggiolo & Kistler, 2014).…”
Section: Introductionsupporting
confidence: 53%
“…material originating from solar wind entering on the dayside). Solar wind ions are also a measurable constituent of the ring current (e.g., Borovsky et al, 1998;Gloeckler et al, 1985) and the middle to outer magnetosphere (Cohen et al, 2017), and so our results are relevant for understanding the composition of these regions as well.…”
Section: Discussionmentioning
confidence: 91%